Pendampingan Pengaplikasian E-Commerce dan Pelatihan Peyusunan Laporan Keuangan Sederhana Pada Ibu Rumah Tangga di Desa Trojalu, Baureno, Bojonegoro - Anita Handayani (Jurnal Pengabdian Manajemen, 2022)
The role of housewives at this time is required to be more active in contributing to the family, namely by thinking more modernly and creatively to be able to help improve family welfare. One of them can be through becoming a career woman or entrepreneurship. However, it is possible that there are still many housewives who have not been able to take advantage of their free time to be more empowered so that they can be useful for the family. So for mothers who have a lot of free time, it is necessary to add insight and skills, so activities that can provide motherhood are needed. household without having to leave the nature of being a housewife, namely in the field of entrepreneurship. The entrepreneurial activities provided in the activity are using e-commerce application activities to provide skills to housewives related to selling online. Then provide training on the preparation of simple financial reports so that housewives are able to manage finances for businesses, which will later be run. Through this activity, housewives can have skills and insights that can be used to play a role in family welfare through entrepreneurship through online media, and be able to manage finances well.